Direito premial trabalhista e compliance na construção de uma teoria da justiça social premial - Daniela Rodrigues Machado Vilela (2021)
The general objective of this thesis is to investigate, without pretending to be finite, the outline of the contours of the Labor Premial Law and also labor compliance, showing that the second is inserted, contained, in the systematization of the first. The present thesis innovates by assuming the construction of a theory of Social Justice Premial Labor that takes place with the effectiveness of labor rights. An analysis will be made of the compatibility of the current moment with the implementation of premium practices in the scope of industrial relations, due to the utilitarian character of prizes and incentives in a society that calls for conditions of existence of workers with greater dignity in a context of evident non-compliance with labor legislation. To decompose the object of study, it starts by contextualizing the assertiveness of the present time with the applicability of these institutes. Discussions will also be made on the default of labor credit and the ineffectiveness of rights, as well as the need for the relationship between capital and labor to become less unequal and inhumane. An analysis will be made of the importance of forming habits to act accordingly, addressing the advantages of a law-enforcement mentality. It is asserted that awarding prizes is a source of motivation for corporations and people towards good action. The validity of language and positive education is an essential element for the construction of a less oppositive, more dignified and human world. Some theories about the ideal of justice and social justice will also be analyzed. It defends the validity and the need for labor rights to materialize, which will provide a theorization of the so-called “social premium labor justice”, which presupposes the possibility that rights in the scope of industrial relations are observed and credits fulfilled, that is, there will be access to justice through rights. Acting in accordance with the law and business regulations is a healthy means of promoting ethics in industrial relations and serves the interests of both parties in an employment relationship, by making it more probable and humane. Finally, the research will end with the contextualization of the premial logic and the demonstration of its importance, as a mechanism capable of transforming social reality through the dissemination of good habits that lead to a perspective that justice in modernity is closely related to the effectiveness of rights. It is fair to enforce rights, comply with labor legislation and what has been agreed. Therefore, knowing and discussing Premial Labor Law is unavoidable, after all, the future is premial.